2018
DOI: 10.1038/s41467-018-03951-0
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen-resistant breast cancer cells are resistant to DNA-damaging chemotherapy because of upregulated BARD1 and BRCA1

Abstract: Tamoxifen resistance is accountable for relapse in many ER-positive breast cancer patients. Most of these recurrent patients receive chemotherapy, but their chemosensitivity is unknown. Here, we report that tamoxifen-resistant breast cancer cells express significantly more BARD1 and BRCA1, leading to resistance to DNA-damaging chemotherapy including cisplatin and adriamycin, but not to paclitaxel. Silencing BARD1 or BRCA1 expression or inhibition of BRCA1 phosphorylation by Dinaciclib restores the sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 40 publications
6
94
2
Order By: Relevance
“…However, the differences in colony formation between MDA‐MB‐468 and MDA‐MB‐231 cells after 4 Gy were not significant 30 . It was recently reported that PI3K/AKT inhibitor inhibited the resistance to endocrine or DNA‐damaging radiotherapy in ER‐positive early patients with BC 31 . Besides, activation of the AKT pathway might also contribute to the radioresistance in BC and glioblastoma cells 13,26 .…”
Section: Discussionmentioning
confidence: 97%
“…However, the differences in colony formation between MDA‐MB‐468 and MDA‐MB‐231 cells after 4 Gy were not significant 30 . It was recently reported that PI3K/AKT inhibitor inhibited the resistance to endocrine or DNA‐damaging radiotherapy in ER‐positive early patients with BC 31 . Besides, activation of the AKT pathway might also contribute to the radioresistance in BC and glioblastoma cells 13,26 .…”
Section: Discussionmentioning
confidence: 97%
“…Hormonal therapy and Her2-targeted monoclonal antibodies have significantly improved the clinical outcome of ER + and Her2 + breast cancer (3,4). However, the relatively low response rate and the development of resistance during treatment limits their therapeutic efficacy in numerous ER + or Her2 + breast cancer patients (5,6). The treatment of TNBC patients depends solely on chemotherapy, which reduces the overall survival rate (7).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, eIF4E might confer tamoxifen resistance via oestrogen receptor independent pathway due to the activity of mTOR and MNK1 [28], one of the downstream modulators being RUNX2 [33] which is found to be important in breast tumour growth and metastasis [34,35]. Moreover, RUNX2 could regulate the WNT/β-catenin and TCF-β signalling pathways, two pathways essential to tamoxifen resistance [36,37]. In tamoxifen-resistant cells, these mechanisms might work together, forming a single or Our study which demonstrates phosphorylation independent eIF4E translational reprogramming of selective mRNAs determining tamoxifen resistance is novel.…”
Section: Discussionmentioning
confidence: 99%